2016
DOI: 10.1103/physreva.93.062322
|View full text |Cite
|
Sign up to set email alerts
|

Quantumness and the role of locality on quantum correlations

Abstract: Quantum correlations in a physical system are usually studied with respect to a unique (fixed) decomposition of the system into subsystems, without fully exploiting the rich structure of the statespace. Here, we show several examples in which the consideration of different ways to decompose a physical system enhances the quantum resources and accounts for a more flexible definition of quantumness-measures. Furthermore, we give a new perspective regarding how to reassess the fact that local operations play a ke… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…It was shown by Hall that the net Fisher information is: IρIγ4D2, where D is the number of dimensions, although this inequality is not general and many examples have been shown to counter Hall's inequality. For example, Bellomo et al have demonstrated that for a free particle Gaussian wave function or its derivative wave function, the I ρ I γ → 0 when t → ∞. Aguiar et al calculated the I ρ I γ for two damped harmonic oscillators namely Lane‐Emden (damping factor scales as t −1 ) and Caldirola‐Kanai (constant damping factor).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown by Hall that the net Fisher information is: IρIγ4D2, where D is the number of dimensions, although this inequality is not general and many examples have been shown to counter Hall's inequality. For example, Bellomo et al have demonstrated that for a free particle Gaussian wave function or its derivative wave function, the I ρ I γ → 0 when t → ∞. Aguiar et al calculated the I ρ I γ for two damped harmonic oscillators namely Lane‐Emden (damping factor scales as t −1 ) and Caldirola‐Kanai (constant damping factor).…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been argued that the quantum discord, and similar other information theoretic measures, actually not only quantifies entanglement, i.e., nonlocal quantumness but also local quantumness [22,23]. For example, due to the presence of local quantumness, the quantum discord (and other related measures [1]) increases by applying certain kinds of local noise [24].…”
Section: Introductionmentioning
confidence: 99%